The need for PCSK9 inhibitors and associated treatment costs according to the 2019 ESC dyslipidaemia guidelines vs. the risk-based allocation algorithm of the 2017 ESC consensus statement: a simulation study in a contemporary CAD cohort. (2nd December 2020) - Blaum, Christopher; Seiffert, Moritz; Goßling, Alina; Kröger, Friederike; Bay, Benjamin; Lorenz, Thiess; Braetz, Julian; Graef, Annika; Zeller, Tanja; Schnabel, Renate; Clemmensen, Peter; Westermann, Dirk; et al.
Abstract: Background: The recently updated European Society of Cardiology (ESC) dyslipidaemia guidelines recommend a lower low-density lipoprotein cholesterol (LDL-C) goal of <55 mg/dL for patients with atherosclerotic cardiovascular disease (ASCVD), with a concomitant Class IA upgrade for proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) for patients not reaching their LDL-C goal under conventional lipid-lowering therapy. Aims: We aim to quantify the need for PCSK9i and the related costs to achieve the revised LDL-C goal in ASCVD patients compared to former ESC recommendations, in particular the risk-based 2017 ESC consensus update. Methods and results: We included patients with ASCVD from an observational cohort study ongoing since 2015. A Monte Carlo simulation incorporating a treatment algorithm adding sequentially a statin, ezetimibe, and a PCSK9i was applied with consideration of partial and total statin intolerance. The need for PCSK9i was calculated for three different ESC recommendations (2019 guidelines, 2016 guidelines, 2017 consensus update). Preventable events and treatment costs due to PCSK9i were calculated for a range of annual event rates from 2% to 8% and annual treatment costs of ca. 6050 €. We included 1780 patients (mean age 69.5 years). Median LDL-C at baseline was 85.0 mg/dL, with 61% of patients taking lipid-lowering medication. The need for PCSK9i was simulated to be 42.0% (ESC 2019), 31.9% (ESC 2016), and 5.0% (ESC 2017). The LDL-C goals were achieved in 97.9%, 99.1%, and 60.9% of patients, respectively. Annual treatment cost for PCSK9i per 1 000 000 ASCVD patients would be 2.54 billion € (ESC 2019) compared to 0.30 billion € (ESC 2017). Costs per prevented event due to PCSK9i initiation differed widely, e.g. 887 000 € for an event rate of 3% and a treatment goal of <55 mg/dL compared to 205 000 € for an event rate of 7% and risk-based use of PCSK9i. Conclusion: The revised LDL-C treatment goals increase the projected need for PCSK9i with a substantial increase in associated treatment cost. An allocation strategy based on residual LDL-C and clinical or angiographic risk factors leads to a more tailored target population for PCSK9i with a reasonable benefit/cost ratio.